UPAYA MENINGKATKAN PEMAHAMAN SISWA PADA OPERASI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT MELALUI METODE DEMONSTRASI MENGGUNAKAN ALAT PERAGA DI KELAS V SDN 002 NONGSA - Yuliati, Yuliati (STKIP PGRI Bandar Lampung, 2021)
This study aims to determine how the efforts to improve students 'understanding of the operation of addition and subtraction of integers through demonstration methods using teaching aids, and whether the use of demonstration methods can improve students' understanding of the operations of addition and subtraction of negative integers. The research method used was classroom action research (PTK). This method is carried out in 4 stages, namely planning, implementing, observing and reflecting. The instruments used were teacher and student observation sheets, test instruments, and field notes. The results showed that the average score of the students' comprehension test results at the end of cycle I was 67, then increased to 78 at the end of cycle II. Meanwhile, the percentage of teacher activity also increased, from cycle I to 72%, and in cycle II to 85%. In addition, student activity also increased from 65% to 82%. Thus it can be concluded that the use of demonstration methods with teaching aids can improve students' understanding of the operations of addition and subtraction of integers.